On-ice return-to-hockey progression after anterior cruciate ligament reconstruction - Capin, J. J.; Behrns, W.; Thatcher, K.; Arundale, A.; Hutchinson Smith, A.; Snyder-Mackler, L. (Journal of Orthopaedic & Sports Physical Therapy, 2017)
Limited literature exists pertaining to rehabilitation of ice hockey players seeking to return-to-sport after anterior cruciate ligament reconstruction (ACLR). The purpose of this clinical commentary is to present a criterion-based, return-to-ice hockey progression for athletes after ACLR. First, we review pertinent literature and provide previously published guidelines on general rehabilitation after ACLR. Then, we present a four-phase, on-ice skating progression with objective criteria to initiate each phase. During the early on-ice phase, the athlete is reintroduced to specific demands, including graded exposure to forward, backward, and crossover skating. In the intermediate on-ice phase, the emphasis shifts to developing power and introducing anticipated changes of direction within a controlled environment. During the late on-ice phase, the focus progresses to developing anaerobic endurance and introducing unanticipated changes of direction, but still without other players or contact. Finally, once objective return-to-sport criteria are met, non-contact team drills, outnumbered and even-numbered drills, practices, scrimmages, and games are progressively reintroduced during the return-to-sport phase. Recommendations for off-ice strength and conditioning exercises complement the on-ice progression. Additionally, we apply the return-to-hockey progression framework to a case report of a female collegiate defensive ice hockey player who returned to sport successfully after ACLR. This criterion-based return-to-hockey progression may guide rehabilitation specialists managing athletes returning to ice hockey after ACLR.